Localizing the SDGs: A Case Study of Collaborative Models between BUM Desa and Pesantren in Central Java - Marimin, Agus; Ardiansyah, Misnen; Indra Jaya, Pajar Hatma (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
Achieving the Sustainable Development Goals (SDGs) at the village level requires collaboration across institutions. However, such collaboration is often hindered by differing institutional orientations and interests. Village-Owned Enterprises (BUM Desa), which aim to strengthen the local economy, hold significant potential for strategic partnerships. Unfortunately, cooperation between BUM Desa and other institutions such as Islamic boarding schools (pesantren), remains limited. Pesantren, as socio-religious institutions, have strong community networks and considerable influence. This study explores a collaboration model between BUM Desa and the Modern Islamic Boarding School (PPMI) Assalam in Sukoharjo Regency. It aims to analyze how these institutions, despite their distinct orientations, work together to support SDG implementation. Using a qualitative case study approach, data were gathered through interviews with BUM Desa managers, pesantren leaders, village officials, and community figures, alongside observations and document analysis. Thematic analysis was conducted through data collection, condensation, presentation, and conclusion stages. Findings reveal nine joint initiatives: four in the economic sector, three in the social sector, and two in the environmental sector. The success of this collaboration is driven by five key factors: (1) initial conditions, (2) institutional design, (3) facilitative leadership, (4) collaborative dynamics such as trust, dialogue, and shared understanding, and (5) tangible outcomes aligned with SDG targets. This study integrates collaborative governance, social enterprise, stewardship, and sharia enterprise theories. Practically, it offers guidance for policymakers and local leaders to develop culturally grounded partnerships that connect economic innovation with social and spiritual legitimacy, accelerating SDG achievement at the village level. Abstrak Mewujudkan SDGs di Tingkat Lokal: Studi Kasus Model Kolaborasi antara BUM Desa dan Pesantren di Jawa Tengah. Pencapaian Tujuan Pembangunan Berkelanjutan (SDGs) di tingkat desa memerlukan kolaborasi antar-lembaga. Namun, kolaborasi ini sering terhambat oleh perbedaan orientasi dan kepentingan kelembagaan. Badan Usaha Milik Desa (BUM Desa), yang bertujuan memperkuat ekonomi lokal, memiliki potensi besar untuk membangun kemitraan strategis. Sayangnya, kerja sama antara BUM Desa dan lembaga lain seperti pesantren, masih terbatas. Padahal, pesantren sebagai lembaga sosial-keagamaan memiliki jaringan kuat dan pengaruh besar di masyarakat. Penelitian ini mengkaji model kolaborasi antara BUM Desa dan Pondok Pesantren Modern Islam (PPMI) Assalam di Kabupaten Sukoharjo. Tujuannya adalah menganalisis bagaimana kedua lembaga dengan orientasi berbeda dapat bekerja sama dalam mendukung implementasi SDGs. Pendekatan kualitatif dengan metode studi kasus digunakan, dengan pengumpulan data melalui wawancara dengan pengelola BUM Desa, pimpinan pesantren, aparat desa, dan tokoh masyarakat, serta observasi dan analisis dokumen. Analisis tematik dilakukan melalui tahapan pengumpulan, kondensasi, penyajian, dan penarikan kesimpulan. Hasil penelitian menunjukkan sembilan inisiatif bersama: empat di sektor ekonomi, tiga di sektor sosial, dan dua di sektor lingkungan. Keberhasilan kolaborasi ini didorong oleh lima faktor utama: (1) kondisi awal, (2) desain kelembagaan, (3) kepemimpinan fasilitatif, (4) dinamika kolaboratif seperti kepercayaan, dialog, dan pemahaman bersama, dan (5) hasil nyata yang selaras dengan target SDGs. Studi ini menggabungkan teori tata kelola kolaboratif, kewirausahaan sosial, stewardship, dan kewirausahaan syariah. Secara praktis, studi ini memberikan panduan bagi pembuat kebijakan dan pemimpin lokal untuk merancang kemitraan berbasis budaya yang menghubungkan inovasi ekonomi dengan legitimasi sosial dan spiritual dalam percepatan SDGs di tingkat desa.